Juvenile Hemochromatosis due to a Homozygous Variant in the HJV Gene - María-Belén; Manuel Méndez; María-Isabel; Ana-María; José-Manuel; María-José (Hindawi Limited, 2022)
Hemochromatosis type 2 or juvenile hemochromatosis has an early onset of severe iron overload resulting in organ manifestation such as liver fibrosis, cirrhosis, cardiomyopathy, arthropathy, hypogonadism, diabetes, osteopathic medicine, and thyroid abnormality, before age of 30. Juvenile hemochromatosis type 2a and 2b is an autosomal recessive disease caused by pathogenic variants in HJV and HAMP genes, respectively. We report a child with hepatic iron overload and family history of hemochromatosis. We aim to raise awareness of juvenile hemochromatosis, especially in families with a positive family history, as early diagnosis and treatment may prevent organ involvement and end-stage disease. The purpose of this study was to identify the gene variant that causes the disease. The genetic study was performed with a targeted gene panel: HFE, HJV, HAMP, TFR2, SLC40A1, FTL, and FTH1. We identified the variant c.309C > G (p.Phe103Leu) in the HJV gene in the homozygous state in the patient.